2021
DOI: 10.1002/adma.202103217
|View full text |Cite
|
Sign up to set email alerts
|

Video Speed Switching of Plasmonic Structural Colors with High Contrast and Superior Lifetime

Abstract: Reflective displays or “electronic paper” technologies provide a solution to the high energy consumption of emissive displays by simply utilizing ambient light. However, it has proven challenging to develop electronic paper with competitive image quality and video speed capabilities. Here, the first technology that provides video speed switching of structural colors with high contrast over the whole visible is shown. Importantly, this is achieved with a broadband‐absorbing polarization‐insensitive electrochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 52 publications
0
70
0
Order By: Relevance
“…[43,46,47] Because the switching speed is strongly dependent on the mobility of the ions in the solid ion gel, there is potential for further improvements by optimizing the electrolyte to obtain higher ionic mobility. [43,47,49] Furthermore, recent research also showed that modified device configurations and use of aqueous electrolytes can boost the switching speed of conducting polymer devices even to video rates. [50] We will now demonstrate that the plasmonic response of conducting polymer nanoantennas can be tuned gradually, in addition to complete electrical on/off switching.…”
mentioning
confidence: 99%
“…[43,46,47] Because the switching speed is strongly dependent on the mobility of the ions in the solid ion gel, there is potential for further improvements by optimizing the electrolyte to obtain higher ionic mobility. [43,47,49] Furthermore, recent research also showed that modified device configurations and use of aqueous electrolytes can boost the switching speed of conducting polymer devices even to video rates. [50] We will now demonstrate that the plasmonic response of conducting polymer nanoantennas can be tuned gradually, in addition to complete electrical on/off switching.…”
mentioning
confidence: 99%
“…Further detailed investigations on the influence of, e.g., oxygen and humidity during electrochemical switching, adjustments to the fabrication process, and electrochemical cell sealing in inert gas environments or the use of solid electrolytes should benefit the overall switching performance. Additionally, conductive polymers have recently proven to be stable for an extremely long time, with little to no degradation over >10 7 cycles at video-rate switching frequencies ( 33 ). Metallic polymers also offer the opportunity to gradually change the carrier density and hence the plasma frequency, which allows for gray-scale operation and thus opens another window of opportunity.…”
mentioning
confidence: 99%
“…In fact, multicolor EC subpixels can be prepared not only by EC materials with different colors, but also by tunable structural colors, as discussed in Section above. Based on this approach, colorful pixels (subpixels) can be easily achieved, which dramatically simplifies the difficulty of color/material design. , For example, Andreas B. Dahlin’s group reported an interesting hybrid material combining CPs and plasmonic metasurfaces (PMSs), and further realized a multicolor electronic paper . The PMSs were composed of a 150 nm silver film (for providing a high reflection basis), an alumina spacer layer (for tuning the reflective color by F–P interference), and a gold film with short-range ordered nanoholes (Figure b).…”
Section: Electrochromic Pixel Displaysmentioning
confidence: 99%